Barreiras n\~ao-tarifárias às exportaç\~oes brasileiras no Mercosul: O caso de calçados - Patrícia Anderson (Instituto de Pesquisa Econômica Aplicada (IPEA), 2001)
– Once the tariff barriers to trade among Mercosur countries were eliminated, government policies other than tariffs became an important trade policy instrument. The main objective of this paper is to identify the non-tariff barriers applied by the Mercosur countries to the Brazilian's footwear exports and it is organized as follows: the introduction; the second part presents the main caracteristics of the footwear industry and its performance in Brazil in the recent years; the third part examines the footwear's international trade; the fourth part discusses some theoretic aspects of the non-tariff barriers (NTB) and indicates the NTB that are applied to Brazilian footwear exports to Mercosur; the last part concludes the paper.
Keywords: 330; Nichttarifäre Handelshemmnisse; Mercosur-Staaten